Ketogena dieta - Bregant, Tina (Zdravniški vestnik, 2009)
Background The ketogenic diet is a high fat, adequate protein, low carbohydrate diet. It has been used in the treatment of intractable childhood epilepsy, difficult-to-control seizures in adults, GLUT1 deficiency syndrome and PDH deficiency. conclusions This review traces a history of ketogenic diet, reviews its uses and side effects, and discusses possible alternatives and the dietćs possible mechanisms of action. We show how to use the diet in practice. Protocol and calculations are presented. We look toward possible future uses of the ketogenic diet, since it is efficient, under doctorćs supervison safe, but very demanding, additional treatment.
Keywords: Diet Therapy; Dietary Fats; dietetika; Dietne maščobe; Energetska presnova; Energy Metabolism; Epilepsija; Epilepsy; ketogena dieta; Ketones; Ketoni